Nutcracker syndrome in a 13-year-old girl with haematuria – case report - Lechańska-Helman, Joanna; Balcerak, Joanna; Malewska-Kaczmarek, Kamila; Kwarta, Paulina; Szadkowska, Agnieszka; Stelmach, Iwona (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Nutcracker syndrome (NCS) is an unusual cause of haematuria and is defined as compression of the left renal vein between the aorta and superior mesenteric artery, resulting in elevation of left renal vain pressure and collateral vein development. Symptoms of NCS include the following: haematuria, abdominal and left flank pain, pelvic congestion syndrome, and orthostatic proteinuria, although, clinically, gross haematuria may be the only disorder. We report a 13-year-old girl who experienced haematuria for two years with chronic back and abdominal pain. Each urinalysis revealed haematuria (20% dysmorphic). In the presented case Doppler ultrasonography revealed left renal vein dilatation up to the angle between the superior mesenteric artery and the aorta with a diameter of 7 mm in the hilar region. NCS can be easily missed by routine tests in children.